Congenital diaphragmatic hernia with hepatic heterotopia - Yasser AlFraih (Elsevier, 2021)
The association of congenital diaphragmatic hernia with hepatic heterotopia is a rare one that has been scarcely reported. We present a case of a female neonate with an antenatally diagnosed left congenital diaphragmatic hernia. Intra-operatively she was found to have ectopic liver tissue within the hernia sac. This case report discusses the presentation, classification, and significance of this rare association.